Caracterização de acessos polimórficos de arroz vermelho do Rio Grande do Sul por descritores morfológicos e microssatélites - Dornelles, Sylvio Henrique Bidel (2009)
This work has for objective to evaluate the phenothypic and genothypic characteristics of different morphologic types of red rice that happen in areas of production of irrigated rice of the State of Rio Grande do Sul - Brazil, for morphologic descriptors and molecular markers, and his response to the use of chemical technology. For this reason, it were conducted two greenhouse experiments and one laboratory study with DNA sequencing of the biotypes. The results allowed to conclude that the biotypes of red rice is hybrided with IRGA 417 cultivar, besides with occurrence of introgression of resistance genes of cultivated Clearfield rice, by gene flow, for biotypes of red rice as the access Catuçaba 1 that presented phenothypic or genothypic characteristics of the cultivated rice IRGA 422 CL and Puitá CL INTA and presence of the mutated acetolactate synthase (ALS) gene for the resistance to the herbicide. It was also observed the occurrence of tolerant biotypes (Rio Pardo 1) or resistant (Catuçaba 1) to the herbicide imazetapir, what turns urgent the use of different strategies of control of the red rice in the State of Rio Grande do Sul - Brazil.